Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1021/ma010744c
|View full text |Cite
|
Sign up to set email alerts
|

NMR Study of Branched Polyethylenes Obtained with Combined Fe and Zr Catalysts

Abstract: The products obtained with the system {[(ArNC(Me))2C5H3N]FeCl2}/MAO (Ar = 2-C6H4(Et)) (1) and the ones obtained by the use of 1 in conjunction with Me2SiInd2ZrCl2/MAO (2) or EtInd2ZrCl2/MAO (3) were completely characterized by 1H NMR and 13C NMR. Catalyst 1 gives mainly linear α-olefins of molecular weights close to 2000 g/mol and a low amount of alkanes. The use of 1 with 2 or 3 using only ethylene as monomer gives branched polyethylene with ethyl, butyl, and mainly long branches. Some amount of unreacted α-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
103
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 154 publications
(111 citation statements)
references
References 23 publications
4
103
0
Order By: Relevance
“…The nomenclature adopted for the polymer backbone and branching carbons is defined by Usami et al, 34 and the branching degree is calculated according to the literature. 7 Analysis of the polymer sample by 13 C NMR shows that the polymer contains degrees of branching, with C 2 , C 4 , and C 6 branches. The density of ethyl branches is 19 per thousand carbons, whereas the densities of butyl and long branches are 6.5 and 0.9 per thousand carbons, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The nomenclature adopted for the polymer backbone and branching carbons is defined by Usami et al, 34 and the branching degree is calculated according to the literature. 7 Analysis of the polymer sample by 13 C NMR shows that the polymer contains degrees of branching, with C 2 , C 4 , and C 6 branches. The density of ethyl branches is 19 per thousand carbons, whereas the densities of butyl and long branches are 6.5 and 0.9 per thousand carbons, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…5 C and v c of 68.3%, a parallel result was also gained (T m ¼ 130. 7 C and v c ¼ 65.3%, Run 1) at varied pressure reaction condition under rac-Et(Ind) 2 ZrCl 2 /MAO system. These results indicate that the branched polyethylene cannot be prepared though changing the reaction pressure in catalytic system rac-Et(Ind) 2 ZrCl 2 /MAO.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the branches of resulting polyethylene was 11.8 when the Ni/Zr molar ratio was 2:7 ( Figure 3), and increased to 14.8 for the Ni/Zr molar ratio of 9:2 ( Figure 4). The 13 C NMR results ( Figures 3 and 4) showed that the branches were mainly ethyl [11], which con¯rmed mainly butylenes formed by the Ni catalyst. According to Table 2, the activity of the Zr catalyst has higher activity in higher Ni/Zr.…”
Section: E®ect Of Ni/zr Molar Ratio On Polymerizationmentioning
confidence: 99%
“…In 1995, Brookhart group found that a single late-transition metal catalytic system could transfer sole ethylene to a high branched polyole¯n [8], and also made a bright in°uence for ethylene oligomerization and polymerization by late-transition metal complexes as catalysts. Recently ethylene polymerization for branched polyethylene by combined catalytic system of two catalysts in-situ is becoming the new interest [6,9,10,11]. The combination of zirconocene and late transition metal catalysts is relied on their same cocatalyst, methylaluminoxane (MAO).…”
Section: Introductionmentioning
confidence: 99%